Gestational diabetes mellitus and subsequent cardiovascular disease in a period of rising diagnoses: Cohort study - Azar Mehrabadi; Ya‐Hui Yu; Sonia M. Grandi; Robert W. Platt; Kristian B. Filion (Acta Obstetricia et Gynecologica Scandinavica)
Abstract Introduction Evidence suggests that gestational diabetes mellitus (GDM) is associated with subsequent cardiovascular disease; however, it is unclear what impact changes in screening and diagnostic criteria have had on the association of GDM with long‐term outcomes such as cardiovascular disease. The purpose of this study was to determine the association between GDM and subsequent cardiovascular disease during a period of rising gestational diabetes diagnosis in England. Specifically, associations were compared before and after 2008, when national guidelines supporting risk factor‐based screening were introduced. Material and Methods We conducted a cohort study using routinely collected data from the Clinical Practice Research Datalink linked to the Hospital Episode Statistics and Office for National Statistics databases. The study consisted of persons aged 15–45 years with a livebirth or stillbirth between 1998 and 2017 and without a history of cardiovascular disease or pre‐pregnancy diabetes mellitus. Cox proportional hazards models, with propensity score weighting using matching weights, were used to estimate adjusted hazard ratios (aHRs) with 95% confidence intervals (CIs) for the association of GDM diagnosis in the first recorded pregnancy with subsequent cardiovascular disease. Results Among 232 315 individuals, the incidence of cardiovascular disease was 6.6 per 1000 person‐years among those with GDM and 2.2 per 1000 person‐years among those without GDM over a mean follow‐up duration of 5.8 years. The overall aHR, 95% CI was 1.91 (1.41, 2.60). Diagnosis of GDM increased over the study period, from 0.7% in 1998–99 to 5.3% in 2017. The effect size was not markedly different in the years before (1998–2007: adjusted HR 2.05, 95% CI 2.05 1.35, 3.12) and after 2008 (2008–2017: adjusted HR 1.79, 95% CI 1.15, 2.80). Conclusions There was a strong association of GDM with cardiovascular disease after accounting for social and demographic factors and multiple comorbidities, and this association was present both before and after 2008, when national gestational diabetes screening criteria were established.